Membangun Perilaku Hidup Bersih Sebagai Program Kerja Mahasiswa KKNT MBKM Kota Bima - Puji Muniarty; Wulandari Wulandari; Ahmad Yani; Sibil Rahman; Jihan Fahira; Putri Patrianim (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
Implementation of community service in addition to the other two dharmas, it is hoped that there will always be an interelection between the university and the surrounding community. Mentoring activities through community service at KKN locations were also continued with gotong royong activities which have become the culture of the Indonesian people. Through MBKM KKNT activities we are required to practice science, technology, and art. We are expected to be motivators and facilitators of development efforts, especially in rural areas. Community service carried out by the author uses the mentoring method through attracting community participation to do mutual cooperation in maintaining the cleanliness of the surrounding environment. The objectives of the activity are; as a solution to reduce the level of slums that occur in Kendo Village. Based on mentoring activities in the form of mutual assistance in realizing clean and healthy living behaviors, it is expected to strengthen community capacity through physical and spiritual health. Mutual cooperation activities as a form of tolerance for humanity are the goals of the Stie Bima KKNT MBKM work program.